Social cost-benefit analysis in Australia and New Zealand. The state of current practice and what needs to be done - Dobes, Leo (ANU Press, 2016)
All is not well with the evaluation of government programs and projects. Resources available to any society are limited. If governments are to increase the well-being of their citizens, they must be able to select and implement the socially most beneficial projects and policies. But many government agencies lack the expertise to carry out a cost-benefit analysis, or even to commission one. Commercial consultants, on the other hand, often have some analytical expertise, but are not immune from adopting approaches that accommodate the proclivities of their client agencies. In order to increase analytical rigour and methodological consistency, this publication urges the adoption of a 'belts and braces' set of protocols for use in project evaluation.